The effect of ICT literacy on the pedagogical competence of physics teachers' - Masrifah Masrifah; Wahyuni Handayani; Nurjannah Nurjannah; Dewi Amiroh (Momentum: Physics Education Journal, 2022)
This study aims to determine the effect of ICT literacy on the pedagogic competence of high school physics teachers in North Maluku. This research is correlational quantitative research. The subjects in this study were 80 high school physics teachers with details of 60 female teachers and 20 male teachers. Data collection on ICT literacy and pedagogic competence of Physics teachers was carried out through tests using ICT literacy questions and pedagogical competencies of knowledge aspects. Furthermore, the re-search data were analyzed using a linear regression test with IBM SPSS 20 software. Based on the results of the study, it is known that the understanding of ICT literacy has a positive effect on the pedagogic competence of physics teachers in the aspect of knowledge. This can be seen from the coefficient value of the variable X of 0.614, which means the magnitude of the influence of X on Y is in a strong category because it has a percentage of 61.4%. The implication of the results of this study is one of the efforts to improve the pedagogic competence of teachers, namely by strengthening their ICT literacy, because the higher the ICT literacy of teachers, the higher their pedagogical competence.